Elastic stable intramedullary nailing in paediatric traumatology at Yopougon Teaching Hospital (Abidjan) - T H Odéhouri-Koudou; J C Gouli; J B Yao Kreh; S Tembély; O Ouattara; K R Dick (Wolters Kluwer Medknow Publications, 2011)
Context : Elastic stable intramedullary nailing has revolutionised the treatment of fractures in children. Aim : To report our experience with this current technique of management of fractures in children. Methods and Materials : A retrospective study of all children with fractures treated by this method from November 2003 to June 2006 at the Paediatric Surgery Department of Yopougon Teaching Hospital, Abidjan, Côte d'Ivoire. Data were recorded from their medical charts regarding demographics, fracture patterns, associated injuries, morbidity, and outcome. Results : A total of 38 children (14 boys; mean age, 11.7 years; range, 9-15 years) with 41 fractures, sited at femur (n=15), humerus (n=8), tibia and fibula (n=6), forearm (n=7), and radial neck (n=5), associated with other injuries in 7 cases, were enrolled in the study. The mean interval for surgery was 6.8 days. Open reduction was required 5 times (12.1%). The hospital stay was in the range 5-12 days. Minor adverse events were 1 (2.4%) early tibial loss of reduction, 3 (7.3%) skin irritations and 2 (4.8%) transient knee limitations. Complications (17.3%) included 2 axial (4.8%) and 1 rotational (2.4%) femoral malunions below 15°; 3 elbow (7.3%) and 1 knee stiffness (2.4%) in openly reduced cases. Solid consolidation was achieved in all cases, with no disturbance in standard union times. At a mean follow-up period of 16 months (range, 9-28 months), all but 3 patients with opened joints recovered full range of motion, and none showed either limp and gait anomalies or re-fracture after removal of wires. Conclusion : Elastic stable intramedullary nailing in children fractures is easy to perform and has little complications if a proper technique is used.